2010
DOI: 10.1007/s11483-010-9161-4
|View full text |Cite
|
Sign up to set email alerts
|

Application of High-Intensity Ultrasounds to Control the Size of Whey Proteins Particles

Abstract: In this paper, we reported a new method to prepare whey protein microparticles via high-intensity ultrasound disruption. Particles morphology was characterized by confocal microscopy, and their size and distribution were analyzed by light scattering technique. Starting whey protein isolate (WPI) exhibited changes in size and distribution according to its concentration. For WPI, 7.5% (w/w) mean size was 0.7 µm, and upon sonication at ambient temperature, the size was reduced up to 0.2 µm showing the particles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 30 publications
2
31
0
1
Order By: Relevance
“…the size of a particle that corresponds to the mean of the intensity distribution. Zavg is beneficial when citing a single average value for the purpose of comparison (Gordon & Pilosof, 2010). Fig.…”
Section: Whey Protein Aggregationmentioning
confidence: 99%
“…the size of a particle that corresponds to the mean of the intensity distribution. Zavg is beneficial when citing a single average value for the purpose of comparison (Gordon & Pilosof, 2010). Fig.…”
Section: Whey Protein Aggregationmentioning
confidence: 99%
“…Z-average size is the primary and most stable parameter produced by the dynamic light scattering cumulant analysis. Its evaluation is beneficial when comparing different treatments performed on the same sample matrix seeking for differences in aggregation quality patterns rather than for descriptive purposes (Gordon and Pilosof 2010). Assuming an exponential aggregation growth, data points were fitted using an exponential growth function (Eq.…”
Section: Aggregationmentioning
confidence: 99%
“…These results show that the aggregation produced by the thermal treatment would prevail over the disruption caused by HIUS application, although sonication would not allow particles to grow continuously as during the thermal treatment. Similarly, Gordon & Pilosof [6] found that heating WPI solutions (12 % w/w, neutral pH) at 85-93°C with simultaneous sonication for 10 min strongly Contrarily, when EW was thermosonicated at pH 3 a strong decrease of the particle size was observed (Fig. 3b).…”
Section: Influence Of Hius Upon Heating (Thermosonication) On Ew Partmentioning
confidence: 54%
“…The size distribution was monomodal, ranging from 79 to 615 nm with a maximum at 220 nm, for the longest processing time of 20 min. Likewise, Gordon et al [6] found that the particle size of WPI solutions at 7.5 % w/w decreased under the effects of ultrasounds at room temperature and this reduction was greater during the first 2 min of sonication, and then leveled off after 5 min of processing. In this regard, Iida, Tuziuti, Yasui, Towata and Kozuka [10] found that depolymerization of starches of different sources using ultrasound was intense during the initial period of 10-30 min and thereafter it proceeded slowly.…”
Section: Influence Of Hius Without Heating On Ew Particle Size Distrimentioning
confidence: 91%
See 1 more Smart Citation